Adaptive control of time-varying systems based on parameter set estimation - Watkins, J.M.; Kiriakidis, K. (Proceedings of the 37th IEEE Conference on Decision and Control (Cat. No.98CH36171), 1998)
Adaptive control of time-varying plants, in the presence of unmodeled dynamics and bounded disturbances, via parameter set estimation is proposed. The set estimator uses normalization and maps the uniformly bounded equation error on parametric error, which characterizes the modeled part of the plant. Based on the information from the set estimator, a switching control criterion selects the parametric vector from a set of nominal model parameters and tunes in the adaptive controller. At the same time, through stabilization against the parametric error, the policy renders the closed-loop modeled dynamics robust with respect to the equation error mechanisms.